the Sistem Pakar Analisis Love Language untuk Menilai Kualitas Komunikasi Pasangan Milenial Menggunakan Forward Chaining dan Certainty Factor: Indonesia - Caniago, Deosa Putra; Tan, Vincent; Pakpahan, Sindy Silvia Soarta; Susyantika, Salsabila Adine; Sulthony, M Rachmat; Aswirawan, Maria Yosefina Meinadia Sekar Kinanti (Computer Science and Information Technology, 2026)
This research aims to analyze the influence of love language on communication quality among millennial couples in Indonesia. Millennials, who are highly immersed in digital interaction, tend to communicate quickly and text-based, making romantic interactions dynamic yet prone to misunderstanding. A quantitative survey was conducted involving 180 respondents aged 22–35 who had been in a relationship for at least one year. A Likert-scale questionnaire measured preferences across the five love language categories—Words of Affirmation, Quality Time, Acts of Service, Physical Touch, and Receiving Gifts, as well as communication quality indicators including openness, clarity, trust, and emotional intimacy. Findings indicate that all five love languages significantly affect communication quality, each with varying levels of influence. Quality Time emerged as the most dominant category with an estimated tendency of 92–96%, followed by Words of Affirmation with a dominance level above 85%. These results suggest that understanding and adapting to one’s partner’s love language can serve as an effective communication strategy to increase emotional closeness, reduce conflict, and strengthen relationship harmony among millennial couples.